Evaluating on-campus haircut and grooming services: insights into student needs, satisfaction, and eco-friendly practices at UiTM - Affendy Lee, Noor Azli; Sulaiman, Suria; Rozli @ Rosli, Mohd Ikmal Fazlan; Abd Ghani, Kay Dora; Zaini, Intan Rabiatulainie (Universiti Teknologi MARA, Kedah, 2024)
The research addresses the gap in understanding university students' needs and preferences for on-campus haircut and grooming services. The primary objective of the study is to evaluate the awareness, usage patterns, satisfaction levels, and interests of students concerning these services. To achieve this, a comprehensive survey was conducted among students from a northern UiTM campus. The survey aimed to gather detailed insights into students' current engagement with grooming services, their satisfaction with these services, and their preferences for future improvements. The survey results indicate a moderate level of awareness among students about existing grooming services on campus. A significant portion of the respondents reported using these services monthly, reflecting a steady demand. Despite this, overall satisfaction with the current grooming services is mixed, with pricing and accessibility highlighted as key areas needing enhancement. Furthermore, the survey revealed a strong interest in the development of a campusbased grooming app or website, suggesting a demand for more streamlined and convenient access to these services. The environmental consciousness of the students was also evident, with many advocating for the incorporation of eco-friendly practices in campus grooming services. In conclusion, this study underscores the need for the implementation of eco-friendly practices and the development of digital platforms to enhance service accessibility. These recommendations aim to better cater to the diverse grooming needs of university students, ultimately enhancing their overall campus experience and well-being.